Discrete tyre model application for evaluation of vehicle limit handling performance. Issue 11 (1st November 2016) - Siramdasu, Y.; Taheri, S.
ABSTRACT: The goal of this study is twofold, first, to understand the transient and nonlinear effects of anti-lock braking systems (ABS), road undulations and driving dynamics on lateral performance of tyre and second, to develop objective handling manoeuvres and respective metrics to characterise these effects on vehicle behaviour. For studying the transient and nonlinear handling performance of the vehicle, the variations of relaxation length of tyre and tyre inertial properties play significant roles [Pacejka HB. Tire and vehicle dynamics. 3rd ed. Butterworth-Heinemann; 2012]. To accurately simulate these nonlinear effects during high-frequency vehicle dynamic manoeuvres, requires a high-frequency dynamic tyre model ( Hz). A 6 DOF dynamic tyre model integrated with enveloping model is developed and validated using fixed axle high-speed oblique cleat experimental data. Commercially available vehicle dynamics software CarSim® is used for vehicle simulation. The vehicle model was validated by comparing simulation results with experimental sinusoidal steering tests. The validated tyre model is then integrated with vehicle model and a commercial grade rule-based ABS model to perform various objective simulations. Two test scenarios of ABS braking in turn on a smooth road and accelerating in a turn on uneven and smooth roads are considered. Both test cases reiterated that while the tyre is operating in the nonlinear region of slip or slip angle, any road disturbance or high-frequency brake torque input variations can excite the inertial belt vibrations of the tyre. It is shown that these inertial vibrations can directly affect the developed performance metrics and potentially degrade the handling performance of the vehicle.